Truncated mu opioid receptors with six transmembrane domains are essential for opioid analgesia - Lu, Zhigang (Anesth Analg, 2018)
BACKGROUND: Most clinical opioids act through mu opioid receptors. They effectively relieve pain, but are limited by side-effects, such as constipation, respiratory depression, dependence and addiction. Many efforts have been made towards developing potent analgesics lacking side effects. 3-iodobenzoyl-6β-naltrexamide (IBNtxA) is a novel class of opioid active against thermal, inflammatory and neuropathic pain, without respiratory depression, physical dependence and reward behavior. The mu opioid receptor (OPRM1) gene undergoes extensive alternative pre-mRNA splicing, generating multiple splice variants that are conserved from rodents to humans. One type of the variants is the exon 11 (E11)-associated truncated variant containing 6 transmembrane domains (6TM variant). There are five 6TM variants in the mouse Oprm1 gene, including mMOR-1G, mMOR-1M, mMOR-1N, mMOR-1K and mMOR-1L. Gene targeting mouse models selectively removing 6TM variants in E11 knockout (KO) mice eliminated IBNtxA analgesia without affecting morphine analgesia. Conversely, morphine analgesia is lost in an exon 1 (E1) KO mouse that lacks all 7TM variants but retains 6TM variant expression, while IBNtxA analgesia remains intact. Elimination of both E1 and E11 in an E1/E11 double KO abolishes both morphine and IBNtxA analgesia. Reconstituting expression of the 6TM variant mMOR-1G in E1/E11 KO mice through lentiviral expression rescued IBNtxA, but not morphine, analgesia. The aim of this study was to investigate the effect of lentiviral expression of the other 6TM variants in E1/E11 KO mice on IBNtxA analgesia. METHODS: Lentiviruses expressing 6TM variants were packaged in HEK293T cells, concentrated by ultracentifigation and intrathecally administrated for three times. Opioid analgesia was determined using a radiant-heat tail-flick assay. Expression of lentiviral 6TM variant mRNAs was examined by PCR or qPCR. RESULTS: All the 6TM variants restored IBNtxA analgesia in E1/E11 KO mouse, while morphine remained inactive. Expression of lentiviral 6TM variants was confirmed by PCR or qPCR. IBNtxA ED50 values determined from cumulative dose-response studies in the rescued mice were indistinguishable from wild-type animals. IBNtxA analgesia was maintained for up to 33 weeks in the rescue mice and was readily antagonized by the opioid antagonist levallorphan. CONCLUSIONS: Our study demonstrated the pharmacological relevance of mouse 6TM variants in IBNtxA analgesia and established that a common functional core of the receptors corresponding to the transmembrane domains encoded by exons 2 and 3 is sufficient for activity. Thus, 6TM variants offer potential therapeutic targets for a distinct class of analgesics that are effective against broad-spectrum pain models without many side-effects associated with traditional opioids.